Pengaruh kesesuaian kompensasi, moralitas individu,Asimetri informasi dan efektivitas pengendalianInternal terhadap kecenderungan kecuranganAkuntansi(Studi Empiris pada Badan Usaha Milik Daerah Kabupaten Temanggung) - Suryaningtyas, Rani, Dr. Fatchan Achyani,SE.,M,Si (2016)
The Tendency of Accounting Fraud in indonesia is not only happen in private sectors but also in public sectors whereas the factors that affect the tendency of accounting fraud are compensation compliance, individual morality, information asymmetry and effectiveness of the internal control. This research aimed to examine 1) the affect of compensation compliance to the tendency of accounting fraud, 2) the affect of individual morality to the tendency of accounting fraud, 3) the affect of information asymmetry to the tendency of accounting fraud, 4) the affect of effectiveness of the internal control to the tendency of accounting fraud in the Temanggung Regency-Owned Corporation (BUMD). The kind of this research in quantitative research with used survey method. The population in this research is all employees who works in the Temanggung Regency-Owned Corporation. The Samples in this research is all employees accounting department and finance departement who works in the Temanggung Regency-Owned Corporation which cover: PD. BPR BKK Temanggung, PD. Apotik Waringin Mulyo, PD. BKK Pringsurat, PT.BPD Jawa Tengah, PD.Air Minum "Tirta Agung", PD. Aneka Usaha, PD. Bumi Phala Wisata. The sampling technique in this research with used purposive sampling that the sample selection based on certain criteria corresponding author desired. The data were analysis techniques used descriptive statistics test, quality data test consisting of validity test and reliability test, classical assumption test consisting of normality test, multicolinearity test and heteroscetasticity test, hypothesis test consisting of multiple regression test, coeficient of determination, F test dan t test. The results showed that: 1) compensation compliance has negative significant affect to the tendency of accounting fraud 2) individual morality has negative significant affect to the tendency of accounting fraud 3) information asymmetry has positive significant affect to the tendency of accounting fraud 4) effectiveness of the internal control has negative significant affect to the tendency of accounting fraud .